Navigating Diversity of the Smart City Initiatives in Indonesia - Rachmawati, Rini; Rohmah, Amandita Ainur (Indonesian Journal of Geography, 2025)
Ths article explores the diversity and dynamics of smart city initiatives in Indonesia by analyzing thevarious strategies implemented. Ths article aims to show how the diversity of smart city initiatives and how smart city strategies respond to global challenges. Ths article is the result of a systematic literature review. The review’s findings suggest that smart city initiatives in Indonesia focus on digital transformation, strengthening regional readiness, the participation and needs of local communities, especially in facing complex and dynamic urban challenges. By implementing smart city strategies, Indonesia has the potential to develop inclusive smart cities.Received: 2024-07-05 Revised: 2024-08-08 Accepted: 2025-04-24 Published: 2025-04-30